Analisis Kualitas Udara dalam Ruangan di Kampus Malalayang Fakultas Kedokteran Universitas Sam Ratulangi Berdasarkan Uji Parameter Fisika - Elisa Liuvita, Dea; Esther Wullur Moningka, Maya; Ryckerens Danes, Vennetia (Journal of Comprehensive Science, 2025)
Poor air quality can cause various health problems, including respiratory problems, allergies, stress, and comfort. By testing air quality using physical parameters such as temperature, humidity, and light intensity, this research can help optimize indoor air quality. This study aims to determine air quality based on physical parameter tests in classrooms at the Malalayang Campus, Faculty of Medicine, Sam Ratulangi University. This research method is observational and descriptive. Descriptive research to get an idea of temperature, humidity, and light intensity directly in the room of the Faculty of Medicine, Sam Ratulangi University using tools such as thermohygrometer and luxmeter. The results of this study compare measurements in 3 conditions, namely before class, during class and after class. It was found that the temperature and humidity were relatively increasing, and the lighting decreased in the temporary conditions of the classroom which had an impact on the comfort of students during learning activities. This study concluded that the physical quality of the air with variables of temperature, humidity, and lighting in the room of the Malalayang Campus, Faculty of Medicine, Sam Ratulangi University is not in accordance with the standards set by the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning the Implementation Regulation of Government Regulation Number 66 of 2014 concerning Environmental Health.